2017
DOI: 10.1002/jctb.5190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation temperature on hydrogen production from xylose and the succession of hydrogen‐producing microflora

Abstract: BACKGROUND Hydrogen production through anaerobic dark fermentation is considered to be a potential biological process for xylose utilization. Temperature is one of the most important environmental factors, however, most studies have been carried out over a small temperature range. Batch tests were carried out to investigate the temperature effect on hydrogen production from xylose using a mixed culture over a wide temperature range (35–65°C). Hydrogen production, metabolite distribution and dynamics of microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Two operating temperatures, mesophilic temperature (35 • C) and thermophilic temperature (55 • C), were employed for fermentative hydrogen production under acidogenic anaerobic dark fermentation in batch mode. Temperature is an essential factor for microbial biodegradation to produce hydrogen and VFAs [43,44]. As demonstrated in Figure 3, at initial pH 7, hydrogen production yields obtained from Chlorella sp.…”
Section: Hydrogen Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two operating temperatures, mesophilic temperature (35 • C) and thermophilic temperature (55 • C), were employed for fermentative hydrogen production under acidogenic anaerobic dark fermentation in batch mode. Temperature is an essential factor for microbial biodegradation to produce hydrogen and VFAs [43,44]. As demonstrated in Figure 3, at initial pH 7, hydrogen production yields obtained from Chlorella sp.…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…Thus, the production of hydrogen depends on the microbes used as inoculum. In our research, as the anaerobic sludge used as inoculum was taken from mesophilic operation conditions, operating at higher thermophilic temperature could lead to some of the microorganisms being inhibited, resulting in decreased microbial community diversity and consequently reduced hydrogen productivity [43,45]. Two operating temperatures, mesophilic temperature (35 • C) and thermophilic temperature (55 • C), were employed for fermentative hydrogen production under acidogenic anaerobic dark fermentation in batch mode.…”
Section: Hydrogen Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on anaerobic biological processes have shown that even small changes in the operating temperature can cause significant changes in microbial community composition and H2 yields [14,19,20]. Temporal temperature fluctuations can also lead to changes in the enzymatic activities, growth rates and/or loss of microbial diversity, which directly affect H2 production [21].…”
Section: Introductionmentioning
confidence: 99%
“…Noike and Mizuno 10 intermittently produced hydrogen by using rice husk with 1.73 mol H 2 /mol hexose, 2.54 mol H 2 /mol hexose, and rice shell with 1.29 mol H 2 /mol hexose. Qiu 11 conducted a batch test to study the effect of temperature on the hydrogen production of xylose using a mixed culture over a wide temperature range. The results showed that several microbial community structures were formed under different temperature conditions, resulting in different metabolic pathways for xylose and hydrogen production capacity.…”
Section: Introductionmentioning
confidence: 99%